PENGARUH GADGET TERHADAP REMAJA DALAM KARYA SENI GRAFIS - Hadi Ihsan, Dr. Budiwirman, M.Pd. Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2017)
The creation aims to visualize the teenager's life is highly dependent on gadgets in doing any activity. The technique used in making this final work is serigraphy technique which is one of the techniques used in the manufacture of graphic arts. After performing a series of processes of creation are long, it creates 10 pieces of graphic art, including: 1) Negligent, 2) Introverts, 3) Cyberbully, 4) Friends, 5) Cyber Crime, 6) Played, 7) Past and Present, 8 ) Games, 9) Brainwash, 10) Dependency. Through the work of the theme of the influence senigrafis gadget terhada premajais expected to evoke the spirit of the work of art, and used as a reference and a reference to create a graphic that better in the future.Keywords: Internet, Teen, Gadget, Serigraphy.